Discovering, Recovering, and Covering-up Canada: Tracing Historical Citizenship Discourses in K–12 and Adult Immigrant Citizenship Education - Pashby, Karen; Ingram, Leigh-Anne; Joshee, Reva (Canadian Journal of Education/Revue canadienne de l’éducation, 2014)
In Canada, cultural diversity has always been a contested cornerstone of citizenship and of citizenship education. In the last decade, a number of provinces, including Alberta and Ontario, have published citizenship and character education documents and social studies curricula in which ideas of cultural diversity are central and shape dominant understandings of nationhood. Meanwhile, the federal government produced its own citizenship education text: a study handbook for adult immigrants taking the citizenship test. Recognizing an interesting opportunity to compare how citizenship and diversity are presented to youth and to adult immigrants, we offer a critical analysis of the extent to which current discourses reflect, revise, or reassert those that were prominent in the past. We find that within educational curricula, liberal social justice discourses are taking a background to those that promote social cohesion and a narrow vision of Canadian identity and history and that de-emphasize progressive ideals of engaging with difference and committing to social action policies. At the provincial K–12 level, a neoliberal understanding of individual development and economic rationales is dominant, while at the federal level, there is also a shift toward neoconservatism that recovers the imperial roots of Canadian citizenship ideals while covering up the strong history of equity, diversity, and civic action.